1999
DOI: 10.1108/02621719910300810
|View full text |Cite
|
Sign up to set email alerts
|

Managerial coaching behaviors in learning organizations

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
223
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 225 publications
(228 citation statements)
references
References 42 publications
1
223
1
3
Order By: Relevance
“…A number of previous studies have noted management as an important component of the learning environment that develops in a workplace (Ellström, 2012;Ellström et al, 2008;Fuller and Unwin, 2004) and have found that under certain conditions, the manager can act as a facilitator of learning (Amy, 2008;Ellinger and Boström, 1999;Ellinger and Cseh, 2007;Wallo, 2008) by, for example, communicating with and engaging in problem solving and reflection on various issues with the staff. However, unlike the present study's focus on the significance of leadership in relation to learning outcomes from a training programme and the transfer of learning to the job, previous studies have focused mainly on leadership support for informal learning in everyday work or on the role of leaders in learning organisations.…”
Section: Main Conclusionmentioning
confidence: 99%
“…A number of previous studies have noted management as an important component of the learning environment that develops in a workplace (Ellström, 2012;Ellström et al, 2008;Fuller and Unwin, 2004) and have found that under certain conditions, the manager can act as a facilitator of learning (Amy, 2008;Ellinger and Boström, 1999;Ellinger and Cseh, 2007;Wallo, 2008) by, for example, communicating with and engaging in problem solving and reflection on various issues with the staff. However, unlike the present study's focus on the significance of leadership in relation to learning outcomes from a training programme and the transfer of learning to the job, previous studies have focused mainly on leadership support for informal learning in everyday work or on the role of leaders in learning organisations.…”
Section: Main Conclusionmentioning
confidence: 99%
“…Instead, the mentor-protégé dyad generally forms a vertical relationship in which the mentor serves as a role model, offering advice and direction [11,68]. In coaching, direct supervisors of coachees or external expert consultants can become coaches, but the coach-coachee dyad aims at a horizontal and cooperative relationship to provide timely feedback for work performance.…”
Section: Managerial Coaching Mentoring and Organizational Commitmentmentioning
confidence: 99%
“…Managerial coaching (i.e., coaching leadership or manager-as-coach) is even more prevalent than the other types of coaching in South Korea [5,10]. Managerial coaching means that line managers facilitate their employees' learning as coach in order to encourage the development of a high-performance work environment [11,12]. More than ever, managers can develop their subordinates within the organization by constructing horizontal and cooperative relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the supporter role, it is possible to see similar patterns in studies within the descriptive approach and the normative leadership approach. Several studies describe leadership as oriented towards encouragement, caring and support (Bass, 2000;Beattie, 2006;Ellinger & Bostrom, 1999). The educator role is also found in previous studies.…”
Section: Discussionmentioning
confidence: 68%